1996
DOI: 10.1111/j.1476-5381.1996.tb15192.x
|View full text |Cite
|
Sign up to set email alerts
|

Release of vasopressin and oxytocin by excitatory amino acid agonists and the effect of antagonists on release by muscarine and hypertonic saline, in the rat in vivo

Abstract: 1 It has been claimed that glutamate is the dominant excitatory neurotransmitter in neuroendocrine regulation. The evidence is derived mainly from in vitro experiments. 2 We have investigated in vivo a possible role of excitatory amino acids (EAAs) in the neural control of release of vasopressin (AVP) and oxytocin from the neurohypophysis. 3 In rats under ethanol anaesthesia in which a diuresis was maintained by a constant fluid load, the i.c.v. injection of glutamate and the synthetic agonists a-amino, 3-hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
7
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 30 publications
4
7
0
Order By: Relevance
“…High sodium excretion is in part a consequence of the natriuretic effect of plasma oxytocin, which was also found to be elevated. These data confirm previous studies which showed that OT is released after hyperosmotic stimulus [41][43].…”
Section: Discussionsupporting
confidence: 93%
“…High sodium excretion is in part a consequence of the natriuretic effect of plasma oxytocin, which was also found to be elevated. These data confirm previous studies which showed that OT is released after hyperosmotic stimulus [41][43].…”
Section: Discussionsupporting
confidence: 93%
“…This phenomenon was partially reversed after retrodialysis of V 1 receptor antagonists ( 37). The opposite action of excitatory amino acids agonists, both under basal conditions or after osmotic stimulation, on hypothalamic release (our findings) and pituitary vasopressin release ( 5, 6, 9, 10) is consistent with these observations. A comparable phenomenon may be involved in the regulation of ACTH secretion.…”
Section: Discussionsupporting
confidence: 90%
“…Several lines of evidence indicate that excitatory amino acids and GABA participate in the regulation of pituitary vasopressin release. Excitatory amino acids agonists stimulate vasopressin synthesizing cells, both in vitro ( 5–8) and in vivo ( 9, 10). It has been demonstrated that intracerebroventricular microinjection of GABA inhibits vasopressin release induced by hypertonic saline ( 11).…”
mentioning
confidence: 99%
“…The release of VP and its excretion can be directly assessed in an in vivo rat antidiuretic bioassay Bisset & Fairhall, 1996). Muscarine chloride, a potent stimulator of VP release in this model, caused a profound but reversible antidiuretic response which was comparable in both normal and transgenic JP17 animals.…”
Section: Antidiuretic Bioassaymentioning
confidence: 98%
“…injections of muscarine chloride (20 ng) or by I.V. injections of sodium nitrosopentacyano (400 mg); these doses have previously been shown to release VP acutely in this preparation Bisset et al 1992;Bisset & Fairhall, 1996). Blood samples were withdrawn from the femoral arterial line via a threeway tap into heparinised tubes, and the plasma separated and frozen for subsequent RIA.…”
Section: Antidiuretic Bioassaymentioning
confidence: 99%